Medicalization of natural childbirth assistance: Profile of pregnancies women in a low-risk maternity hospital - Aquino, Alessandra Guimarães (2023)
Introduction: Birth has experienced changes in the understanding of childbirth as a natural process, making it amenable to interventions, such as those related to shorten the labor time by medication. Objective: to describe the prevalence of the use of drugs, instruments, and protocols in the labor and delivery profile of assistance in a public maternity hospital that nurses low risk pregnancies. Method: This is a cross-sectional, descriptive, exploratory, and quantitative study with population (n=26 health professionals). The sociodemographic characteristics of nurses and doctors who provide direct assistance during childbirth were analyzed in addition to those related to the use of medications, instruments, and protocols. Data were tabulated in the Epiinfo 7.2.2.2 program; then, a descriptive statistical analysis was performed. Results: it was observed that 53.8% are obstetric nurses and 46.2% are obstetricians. Among the interviewees: 65.4% assured that they always or almost always completed the partograph, 61.6% always or almost always applied the Bishop index, 57.7% used medication to induce labor. The prevalence of professionals who stated that there were no childbirth care protocols in the institution totaled 80.8%. Conclusion: the present study was relevant to demonstrate that most professionals did not use drugs for labor induction; they considered the integrity of the membranes before these drugs; and, when induction was needed, there was a higher prevalence of the use of oxytocin in relation to misoprostol in cases with the same conditions of the uterine cervix. Most professionals said that they still use childbirth care protocols although they are not institutional.